Forestry harvest planning considering social impacts and soil compaction issues - Rossit, Daniel Alejandro (2022)
Forest harvest planning implies great challenges for wood supply companies. This type of planning involves complex decision processes involving different stakeholders, as well as factors outside the stakeholders that directly affect the resolution of the problem. Within these factors that affect, one of special interest is the conditioning by risk of soil compaction. This factor can be decisive in planning since it functions as a restriction or prohibition on harvesting operations. This phenomenon depends on the hydrological balances of the soils, which in turn depends on the meteorological and climatic conditions. That is why to properly address these decision processes, stochastic approaches are required. On the other hand, there exists a large number of SMEs and micro-SMEs that are dedicated to forest harvesting operations, which work as contractors for industries and provide. These companies have a direct interference in the industrial matrix and in the labor offer in the regional economy of the Argentine Northwest. However, a purely utilitarian approach to forest harvesting would tend to prioritize the hiring of larger companies with superior technical capacity, which would allow production costs to be reduced. However, this would impede the possibility of growth of the regional economy, leaving out smaller companies, which do not have the resources for technological migration. This issue has gained relevance after United Nations included this topic in its Sustainable Development Goals agenda (ODS 8).To contribute to this line, an approach based on mathematical programming is proposed that allow addressing the stochastic complexity of the problem (due to the risk of soil compaction), but that balance the workload delivered to each contractor, ensuring compliance with the demand. For this, a goal programming model is developed, which contemplates the minimization of costs and the balancing of the workload among contractors.